2007
DOI: 10.1002/art.22461
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal power Doppler ultrasonographic assessment of joint inflammatory activity in early rheumatoid arthritis: Predictive value in disease activity and radiologic progression

Abstract: Objective. To evaluate the sensitivity to change of power Doppler ultrasound (PDUS) assessment of joint inflammation and the predictive value of PDUS parameters in disease activity and radiologic outcome in patients with early rheumatoid arthritis (RA). Methods. Forty-two patients with early RA who started therapy with disease-modifying antirheumatic drugs underwent blinded sequential clinical, laboratory, and ultrasound assessment at baseline, 3 months, 6 months, and 1 year and radiographic assessment at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
206
0
15

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 356 publications
(235 citation statements)
references
References 41 publications
8
206
0
15
Order By: Relevance
“…Persistent synovitis, especially in patients with early and very early RA, was proven to be present in patients being considered in clinical remission and was associated with a more unfavourable prognosis [15,22,26,32]. Analysing anti-RA33 titre, depending on US findings, we established statistically significant differences, between patients with/without active synovitis; thus, we found active synovitis only in 3 of the 15 patients with an anti-RA33 titre over the threshold value.…”
Section: Conflict Of Interest: Nonementioning
confidence: 65%
See 1 more Smart Citation
“…Persistent synovitis, especially in patients with early and very early RA, was proven to be present in patients being considered in clinical remission and was associated with a more unfavourable prognosis [15,22,26,32]. Analysing anti-RA33 titre, depending on US findings, we established statistically significant differences, between patients with/without active synovitis; thus, we found active synovitis only in 3 of the 15 patients with an anti-RA33 titre over the threshold value.…”
Section: Conflict Of Interest: Nonementioning
confidence: 65%
“…Setting an antibody profile, highly specific and sensitive, with a diagnostic and prognostic value, could be essential for assessing remission [1,[22][23][24][25][26]. Besides anti-CCP antibodies, present very early in the course of the disease, anti-RA33 antibodies can constitute an additional marker, not only for improving diagnosis, but also for assessing the prognosis and therapeutic response [5,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Of 3004 studies identified initially, 14 articles were selected to be included in the review 8,9,14,25,26,27,28,29,30,31,32,33,34,35 . Table 1 shows the study design characteristics of the studies.…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
“…Power Doppler sonography (PDS) enables the visualization of synovial vascularity and has the ability to represent local inflammation numerically (5). PDS has been reported as a useful tool to detect arthritis in the early stages and monitor disease activity (6,7). PDS has been studied as a clinical device having the potential to provide supplemented joint information in clinical practice (8,9).…”
Section: Introductionmentioning
confidence: 99%